EFEKTIFITAS, EFISIENSI DAN KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI DAERAH PROVINSI MALUKU UTARA - Zainuddin Zainuddin (Universitas Musamus,Merauke,Papua, 2016)
This aim of this research is (1) the effectiveness of local taxes at North Maluku Province (2) the efficiency of local taxes at North Maluku Province, and (3) the contribution of local taxes against original regional income at North Maluku Province through 2010-2014. This research used descriptive quantitative method. Data collection technique come through documentation. The data analysis used in this research are the analysis of efficiency, effectiveness analysis and contribution analysis. The results of this research are: (1) The level of effectiveness of local tax for 5 years at the level of effective. (2) The efficiency rate for local tax during 2010-2014 in the category were efficient. (3) The contribution of local tax againt original regional income North Maluku Province for 5 years very contribute.